2016
DOI: 10.1038/srep38825
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Glucocorticoid-induced Leucine Zipper (GILZ) increases susceptibility to Imiquimod-induced psoriasis and involves cutaneous activation of TGF-β1

Abstract: Psoriasis vulgaris is a chronic inflammatory skin disease affecting millions of people. Its pathophysiology is complex and involves a skin compartment with epidermal and immune cells which produce cytokines, e.g. belonging to the IL-23–Th17-cell axis. Glucocorticoids (GCs) are the most common therapeutics used in cutaneous inflammatory disorders and GC-induced leucine zipper (GILZ) has emerged as a mediator of GCs due to its anti-inflammatory actions, theoretically lacking GC side-effects. We evaluated whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 44 publications
0
22
1
Order By: Relevance
“…In particular, many efforts have focused on the use of GILZ as a more specific downstream mediator of GC action, which would theoretically lack undesired side-effects [ 90 ]. However, there are apparently contradictory results regarding the role of this GC target in skin inflammation as Gilz −/− mice and transgenic mice with generalized overexpression of GILZ were more susceptible to imiquimod-induced psoriasis [ 95 , 96 ].…”
Section: Gr and Mr In Adult Skin Homeostasismentioning
confidence: 99%
“…In particular, many efforts have focused on the use of GILZ as a more specific downstream mediator of GC action, which would theoretically lack undesired side-effects [ 90 ]. However, there are apparently contradictory results regarding the role of this GC target in skin inflammation as Gilz −/− mice and transgenic mice with generalized overexpression of GILZ were more susceptible to imiquimod-induced psoriasis [ 95 , 96 ].…”
Section: Gr and Mr In Adult Skin Homeostasismentioning
confidence: 99%
“…Recent research has demonstrated that GILZ is lacking during chronic inflammation and the inflammation arising from trauma [17,18], and that it exerts anti-inflammatory and immunosuppressive effects in these diseases. The biological activity of a full-length GILZ fusion protein has previously been described [19][20][21][22]. Our previous studies have found that full-length GILZ suppressed ICAM-1 and MCP-1 expression by dephosphorylating NF-κB p65 in retinal endothelial cells in vitro [23] and inhibited LPSinduced retinal inflammation in rats in vivo [10].…”
Section: Discussionmentioning
confidence: 90%
“…Both S12 and S14 also upregulated the AP-1 transcriptional regulators FosB and ATF3 in gene arrays. These genes have previously been demonstrated to be downregulated in non-lesional psoriatic skin compared with normal skin, thus suggesting that even non-lesional skin in psoriasis patients may have disturbances in ceramide metabolism and that this disturbance may predispose skin to psoriatic inflammation 8 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings have direct relevance to human psoriasis. S100A8 is upregulated by some of the current treatments for human psoriasis, namely glucocorticoids and UVA 40 , 42 , 43 . We believe this to be a compensatory upregulation of S100A8 and related molecules in response to treatment, which may be a mechanism of resistance to anti-psoriatic therapy.…”
Section: Discussionmentioning
confidence: 99%